PERBEDAAN PENGARUH PENDEKATAN PEMBELAJARAN SISTEM TERPUSAT DAN ACAK TERHADAP KEMAMPUAN BERMAIN TENIS LAPANGAN DITINJAU DARI KELINCAHAN - IWAN ARYA KUSUMA (Universitas Tunas Pembangunan, 2012)
The purposes of this study are investigating of : (1) the effect differencebetween the teaching approach with block and random systems to the increasement of tennis ability, (2) increasement difference of the tennis abilityamong group who has the good, medium, and lack levels of agility,3) the interaction effects between teaching approach and the level of agility. The increasement of tennis abilityt is computed by substracting the final test score with the initial one.The agility classification was determined by measuring the level of agility by dodging run test. This research used the experimental method with 2 X 3 factorial design. The sixty college students of The Tunas Pembangunan University as samples. They were divided into six experimental groups andwere drawn by random sampling technique. There wastwo independent variables and a dependent variable. Dependent variable was as a response variable. It was an increasement of tennis ability. The first independent variable was teaching approach, with two levels. They were teaching approach with block andrandom system. The second was agility, with three levels, good, medium, and lack levels. This study was held in The Tunas Pembangunan University, Surakarta. The technique for gathering the data used test and measurement.They were Hewitt’s tennis acheivement test anddodge run test.Whereas for analyzing the data used The Two Ways Analysis of Variance. All statistical computation and analysis used Statistical Software Minitab 16 and Spreadsheed Software (Microsoft Excel 2010). The results of this study show :to the increasement of the tennis ability: (1) There was a significant difference of the effect betweenteaching approach with block and random systems. The effect of the second teaching approach was better than the other. Fobs = 5,13, p (= 0,28) < 0,05. The average of tennis ability increasementwith block system treatment was 37,50. (2) There was a significant difference of the tennis ability increasementamonggroups who has the good, medium, and lack levels of agility. Fobs = 23,33, p (= 0,000) < 0,05. The agility good level group’sability increasement wasthe best one with average of increasement 40,90, the medium level group reachedincreasement average 35,15, while the lack level was 33,20. (3) There was interaction between the teaching approach and the agility level. Fobs = 29,60, p (= 0,035) < 0,05. The good level of agilitygroup with the teaching approach by random system got the best increasement with average score 45,50, while the lack level group with the teaching approach by random system got the lowest, with average score 29,20.